Stories from the Middle East - Power - Bechar, Ayelet (Bechar, Ayelet, 2006)
Verzio FF Submission “Power” is the story of a young Bedouin man from a remote village who decides to volunteer to serve in the Israeli army hoping that by doing so he will help bring electricity to his home and save his sick sister